Os passeriformes da Mata Atlântica seguem a regra de Bergmann? - Silva Neto, Edvaldo Nunes da (2015)
The main goal of this research is to test the Bergmann Rule in its levels - order, suborder and parvordem - in contrast with the leading families (Furnariidae, Thamnophilidae, Tyrannidae e Thraupidae) passerines of the Atlantic Forest. I intended to identify whether the pattern of body size distribution in these groups follow this rule. To reach the goal, the Atlantic Forest was divided into 123 squares (110km x110km). So, I calculated the average body size and the passerines richness in each square. Environmental variables employed as predictors were temperature, precipitation and space. The analysis of Linear Regression and, MantelCorrelationwere used. I observed that passerines are positively correlated to temperature and precipitation. On the other hand, latitude is not correlated to Passeri nor to Tyrannidae. I concluded that, in general, all Atlantic Forest passerines follow the Bergmann Rule are in consonance with the Bergmann Rule. In general, researches test/employ the Bergman Rule in more global patterns for passerines. So, we found no previous researches focusing specifically on the Atlantic Forest. In this light, this research is meaningful to this geographic scale, especially because of the uniqueness of this South America ancient ecosystem, the Atlantic Forest.